Molecular detection of protozoan parasites infecting Apis mellifera colonies in Japan. Issue 1 (7th September 2012) - Morimoto, Tomomi; Kojima, Yuriko; Yoshiyama, Mikio; Kimura, Kiyoshi; Yang, Bu; Peng, Guangda; Kadowaki, Tatsuhiko
Summary: The role of protozoan parasites in honey bee health and distribution in the world is not well understood. Therefore, we carried out a molecular survey for the presence of Crithidia mellificae and Apicystis bombi in the colonies of both non‐native Apis mellifera and native Apis cerana japonica in Japan. We found that A. mellifera, but not A. c. japonica, colonies are parasitized with C. mellificae and A. bombi . Their absence in A. c. japonica colonies indicates that A. mellifera is their native host. Nevertheless, the prevalence in A. mellifera colonies is low compared with other pathogens such as viruses and Nosema microsporidia. Japanese C. mellificae isolates share well‐conserved nuclear‐encoded gene sequences with Swiss and US isolates. We have found two Japanese haplotypes (A and B) with two nucleotide differences in the kinetoplast‐encoded cytochrome b sequence. The haplotype A is identical to Swiss isolate. These results demonstrate that C. mellificae and A. bombi distribute in Asia, Oceania, Europe, and South and North Americas.